Development and Approbation of The Methodology for Analyzing the Attitude of the Subjects of the Educational Process to the Formation of Physical Culture in Universities - Bekchanov Ma'mur Tokhir ugli (Periodica Journal, 2023)
In recent years, our state has paid great attention to the physical education of students. Sport has become one of the priorities of state policy. But, despite the development of sports infrastructure, the allocation of colossal funds to promote a healthy lifestyle and increase the number of people systematically involved in physical education and sports at a meeting on the development of the physical education system in Uzbekistan. It can be said that physical culture still remains on the sidelines of the educational and upbringing processes. The purpose of the article is to study the model of managing the process of forming a conscious constructive attitude to the problems of physical culture in all subjects of the educational process at universities.
Keywords: culture of personality; personality; culture